Sexual violence and neonatal outcomes: a Norwegian population-based cohort study. Issue 10 (14th October 2014) - Henriksen, Lena; Schei, Berit; Vangen, Siri; Lukasse, Mirjam
Abstract : Objective: The objective of this study was to explore the association between sexual violence and neonatal outcomes. Design: National cohort study. Setting: Women were recruited to the Norwegian Mother and Child Cohort Study (MoBa) while attending routine ultrasound examinations from 1999 to 2008. Population: A total of 76 870 pregnant women. Methods: Sexual violence and maternal characteristics were self-reported in postal questionnaires during pregnancy. Neonatal outcomes were retrieved from the Medical Birth Registry of Norway (MBRN). Risk estimations were performed with linear and logistic regression analysis. Outcome measures: gestational age at birth, birth weight, preterm birth (PTB), low birth weight (LBW) and small for gestational age (SGA). Results: Of 76 870 women, 18.4% reported a history of sexual violence. A total of 4.7% delivered prematurely, 2.7% had children with a birth weight <2500 g and 8.1% children were small for their gestational age. Women reporting moderate or severe sexual violence (rape) had a significantly reduced gestational length (2 days) when the birth was provider-initiated in an analysis adjusted for age, parity, education, smoking, body mass index and mental distress. Those exposed to severe sexual violence had a significantly reduced gestational length of 0.51 days with a spontaneous start of birth. Crude estimates showed that severe sexual violence was associated with PTB, LBW and SGA. When controlling for the aforementioned sociodemographic and behavioural factors, the association was no longer significant. Conclusions: Sexual violence was not associated with adverse neonatal outcomes. Moderate and severe violence had a small but significant effect on gestational age; however, the clinical influence of this finding is most likely limited. Women exposed to sexual violence in this study reported more of the sociodemographic and behavioural factors associated with PTB, LBW and SGA compared with non-abused women.